Politik Kebijakan Islamisasi Mahathir - NURHASANAH NURHASANAH (Jurnal Dialog, 2017)
Mahathir leadership era has been marked by his larger and substantive interest to carry Islam on the goverment policy and various programs. It is said that Islamization policy which Mahathir speed up basically does not only spring from goverment intrinsic impetus to promote Islam, but also external political pressures. This article discusses the mount of Islamization policy in Malaysia, especially in Mahathir era; and poins out the conditions that underly his policy